Structural and chemical modifications of oxides and OH generation by space weathering: Electron microscopic/spectroscopic study of hydrogen-ion-irradiated Al2O3. (15th December 2021) - Igami, Yohei; Muto, Shunsuke; Takigawa, Aki; Ohtsuka, Masahiro; Miyake, Akira; Suzuki, Kohtaku; Yasuda, Keisuke; Tsuchiyama, Akira
Abstract: Minerals on airless bodies exhibit characteristic spectral features such as darkening and reddening. Such space weathering is mainly due to hydrogen-ion irradiation by the solar wind and to micrometeorite impacts. Because of the reactivity of hydrogen, the associated H-implantation into O-bearing minerals can lead to the formation of new chemical bonds and may contribute to formation of water. However, laboratory studies still conflict about production efficiency of water and relevant H-bearing molecules such as OH formed by the H-ion irradiation. The production efficiency of the molecules within minerals may be influenced by short-range structural order of the host minerals. It is thus important to clarify how the implanted H interacts with various irradiation defects produced by H-ion bombardment. Here, we investigated H-ion-irradiated alumina (Al2 O3 ), one of the most basic oxides, using scanning/transmission electron microscopy (S/TEM) and electron energy-loss spectroscopy (EELS). The TEM images revealed dense dislocations, nanoscale voids and nanoscale cracks—instead of amorphization—in the region subject to high energy deposition. Our analyses by STEM–EELS hyperspectral imaging (HSI) isolated a few essential spectral components, suggesting that chemical interactions between the implanted H and the host alumina resulted in local generation of OH species rather than amorphization. We also found a spectral feature which may be explained by H2 gas, presumably remaining in the nanovoids, most of which escaped through fractures formed by the coalescence of the high-pressure H2 nanobubbles. Such fractures/crack surfaces can act as additional reactive sites for the formation of the OH species. The present results strongly imply that H + irradiation can be a source of water in minerals in various astrophysical conditions. The present methodology can be applied to a wide range of extraterrestrial materials, such as regolith grains, interplanetary-dust particles, and/or presolar grains in primitive meteorites.